PERBEDAAN STATUS KESEHATAN JARINGAN GINGIVA PADA TIAP-TIAP TRIMESTER USIA KEHAMILAN PADA IBU HAMIL DI PUSKESMAS BUMIAYU BREBES - Santoso, Bedjo; Sutomo, Bambang; Ngadiyono, Ngadiyono (UPPM Poltekkes Kememterian Kesehatan, 2015)
Most pregnant women are still found lazy oral hygiene like brushing your teeth regularly and in the right way. As a result of gum tissue susceptible to infection. If the gums are attacked by germs will occur so inflamed gum infec-tions, commonly called gingivitis (Machfoedz, 2008). There are hormonal changes during pregnancy. The study aims to determine the differences in the health status of gingival tissue in each trimester of gestation in pregnant women in health centers Bradford Brits. This type of research is quantitative descriptive, cross-sectional approach. The independent variable in this study was trimester of gestation and depen-dentnya variable is the health status of gingival tissue. The population in this study consisted of pregnant women the first trimester, second trimester, third trimester, amounting to 337 people. To determine the number of samples is determined as much as 10% of the population of 337 pregnant women, so that the results of the calculation, the number of 34 samples. Stratified sampling technique sampling sample is divided into levels or strata (Arikunto, 2002). Data analysis will be performed by uni-variate and bivariate. Bivariate test with comparative test using independent t-test. The results showed that the state of the gum tissue status in pregnant women in the first trimester is either 8 (73%), the second trimester in a bad criterion (64%), the third trimester in a bad criterion (58%). Test results with independent t-test was obtained p. value = 0.048, shows that there are differences in the incidence bermakana gingival health status in each trimester of pregnancy. Advice to pregnant women, especially for the second and third trimesters should pay more attention to the health condition of the teeth and mouth, drink water, eat it the fruit, vegetables and protein-rich meal, calories and energy. Routine dental and oral health check since the first trimester.